SEVERITY DETERMINANT OF COVID-19 WITH COMORBID HYPERTENSION IN PALEMBANG - Mariana Mariana; Emma Novita; Eddy Roflin (Majalah Kedokteran Sriwijaya, 2022)
Hypertension is a risk factor for disease severity in COVID-19 patients. Data collected from the COVID-19 Handling Task Force as of October 13, 2020, as many as 13.2% of patients who died had comorbid hypertension. This research is an analytic observational study with a cross sectional design. This study uses primary data obtained through observation and questionnaires distributed to COVID-19 patients in Palembang. Most respondents aged 18-25 years (43.5%), female (56.5%), tertiary education level (79.6%), work as civil servants (30.6%) , and domiciled in Ilir Barat I District (14.8%), there are 24 subjects who have comorbid hypertension (22.2%) There are 26 subjects infected with COVID-19 without symptoms (24.1%), 55 subjects with a mild degree ( 50.9%), 23 subjects with moderate (21.3%), and 4 subjects with severe (3.7%) There is a significant relationship between comorbid hypertension and the severity of COVID-19 with a p value = 0.033. Hypertension is 2.8 times more at risk of contracting severe COVID-19 compared to mild and asymptomatic degrees.